Biophysics and its scientific data in industrial product design: جاسم خزعل العقيلي -علاء نجم عبود (Al-Academy, 2020)
The current research discussed biophysics data as a theoretical and applied knowledge base linking industrial design with the natural sciences at the level of applied strategies through which we can enrich the knowledge base of industrial design. The research focused on two main aspects of the scientific references for biophysics, namely: electromagnetism, and biomechanics. According to the performance and functional applications in designing the functions of industrial products at the electromagnetic level, it was found that remote sensing applications: such as fire sensors that were adopted from the insect (Black Beetle) and that their metaphors enable them to hear fire, and collision sensors, which were adopted from the insect (locust) , And its ability to fly in large swarms without colliding with one another, and the location echo sensors that were adopted from (bats), which moves without having a sense of sight, and sound sensors that were adopted from (dolphins). we found that all of these biological features broadened the designer’s understanding of the biological world, and the breadth of knowledge base of industrial designer, which enabled him to design products bearing solutions to problems that were not easily solved without understanding the biological structures of these organisms. In terms of biomechanics, it was found that the processes of analyzing and interpreting the nature and structures of humans and insects, according to the nature of the mechanical structures of each of them, enabled the designer to find many types of products based on adopting the nature of the structural composition of these organisms, which strengthened the possibility of physical application of New ideas and solutions to problems that were not easy to solve without a good understanding of what biophysics is and how living things interact in their natural environments.